ANALISIS PENGARUH INFRASTRUKTUR TERHADAP PENDAPATAN ASLI DESA (STUDI KASUS DI PEDESAAN PULAU MADURA) - Melati Puspa Anugrah (Jurnal Ilmiah Mahasiswa FEB, 2015)
Infrastructure have important role in economic development. It’s not only serve the necessity of region’s economic, but also stimulate new economic activites on certain region. Development if infrastructure can increase region’s economic. The availability of proper infrastructure is inseparable from village government influence. Decentralization has made the concept that development should be directed at the lowest level in goverment structure i;e, village. Village is autonomous region and gain privileges to manage finances, fund allocation village, village chief elections and development process. The objectives of this research is the availability of the infrastructure (roads, water supply, irrigation, electricity, health and education infrastructure) have an influence in the original revenue village (PADesa) using secondary data that obtained through 2014 and PODES survey and using logistic regression analysis. The result of this research showed that the variable irrigation, electricity and health infrastructure showed significan positived results against PADesa. With the result, one of the efforts to improve the results of the PADesa can be done with increasing access to irrigation, electricity and health infrastructure. Keywords : Rural, Disparity, Infrastructure, and PADesa